Electromagnetic fields policy implications for risk assessment - Farag A.; Hussain H.; Said I.; Ahmad A.S. (2023)
The goal of the electromagnetic fields research program is to provide information on the types and extent of human exposure to such fields, as well as guidelines and methods to measure, characterize and manage field exposures. This paper explores the implications of such research for the risk assessment. The policy implications of an exposure are explored after all the data have been gathered and reviewed. This paper shows how risk assessment, exposure assessment and engineering information can be "packed" to address concerns of contributors of EMF policy. It gives a basic decision tree outlining the types of decisions to be encountered. Decisions will have to be taken regarding mitigation options, the certainty of hazard, dose-response relationships and dose-frequency distribution after mitigation. Since risk is a multidimensional concept, therefore, issues concerning electric and magnetic fields need to be addressed by social and political actions beside exposure reduction.